2009
DOI: 10.1136/bjo.2008.152595
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of atypical birefringence pattern in scanning laser polarimetry

Abstract: Axial length or spherical error is a significant predictor for ABP with both GDx VCC and GDx ECC. Caution should be exercised in interpreting the results of scanning laser polarimetry in eyes with a long axial length or myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…Similar results are reported by Wang et al 19 Previous studies have found associations between predictor variables. Qiu et al 21 reported a significant negative correlation between the axial length and TSS. Morishita and associates also found significantly lower TSS in highly myopic eyes compared with moderately myopic eyes.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results are reported by Wang et al 19 Previous studies have found associations between predictor variables. Qiu et al 21 reported a significant negative correlation between the axial length and TSS. Morishita and associates also found significantly lower TSS in highly myopic eyes compared with moderately myopic eyes.…”
Section: Discussionmentioning
confidence: 97%
“…[12][13][14] However, despite the improved technique, uncompensated ARPs remain in some subjects (for example, see Ref. 15). Improved knowledge of the origin of ARP in GDxVCC is useful for basic research into the interaction of light with retinal layers and for clinical applications.…”
mentioning
confidence: 98%
“…16 Advanced SLP devices with ECC showed a significantly lower rate of ABP compared with devices with VCC. 16,17 The GDx ECC was not available until recruiting one third of subjects, hence we Limitations of the present study were a selected study population of a university eye hospital and no age-matched groups (glaucoma, OHT, and normal subjects). To reduce the influence of age, we used an ANCOVA with age as continuous covariate to compare ONH, RNFL, and GCC parameter values.…”
Section: Discussionmentioning
confidence: 93%